PEMIKIRAN MUHAMMAD SYAHRUR; TEORI NADZARIYAH HUDUD DAN APLIKASINYA - Fitrah Sugiarto; Avif Alfiyah; Harni Ratna Tara (UIN Mataram, 2021)
One of the great thinkers in the contemporary era is Muhammad Syahrur, a Syrian liberal Islamic figure. Through his controversial works, al-Kita>b wa al-Qurâ€™a>n: Qira>â€™ah Muâ€™a>shirah, (al-Kitab and al-Qurâ€™an: a Contemporary Reading) Syahrur introduces a new theory of Quranic interpretation, called as the theory of limits. He asserts that the theory of limits is an approach within ijtihad (individual interpretation) to study the muhkama>t verses (clear and direct verses of law) of the Qurâ€™an. The term limit (hudu>d) used by Syahrur refers to the meaning of â€œthe bounds or restrictions of God which should not be violated, contained in the dynamic, flexible, and elastic domain of ijtihad.â€. By using the descriptive-analytical method, the article is talking about the contribution of the theory of limits in qurâ€™anic interpretation that makes significant contributions to the enhancement of Qurâ€™anic studies.